The CAD Modelling Possibilities of Gear Pairs by Two Ways in the Mechanical Engineering Practice - Bodzás, Sándor; Békési, Zsolt; Kertész, József; Szorcsik, Tamás (International Journal of Engineering and Management Sciences, 2021)
The GearTeq 2021 software is a complex gear designer software which is capable to design different types of gears based on the initial geometric parameters by the user. Naturally, the users’ appropriate knowledge for the gear theorem and the manufacturing technology is indispensable for the design. The possibilities of the software are shown in this publication. The designed gear pairs are usable for different engineering fields (robots, working machines, vehicles, etc.).